Dialogue Summary: Designing Integrated Approaches to Support People with Multimorbidity in Ontario - Wilson, MG; Lavis, JN (My University, 2013)
A summary of what was learned from a stakeholder dialogue that addressed problems related to approaches to support people with multimorbidity, options for addressing these problems, key implementation considerations, and next steps for designing integrated approaches to support people with multimorbidity in Ontario.
Keywords: multimorbidity; Ontario